THE CONCEPT OF URBAN METABOLISM - Міхно, О.; Патракеєв, І. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Considered in the article the concept of the metabolism of the urban environment, helps in conducting research in such areas as reducing the burden on the environment, the weakening of environmental problems, reducing our dependence on fossil natural resources. The essence of the concept is that the urban environment is a living organism in which continuous conversion and transformation of energy, material and information flows. Methods and models of metabolic processes will allow to put into practice the concept of sustainable development of the urban environment, which is the development of the doctrine of V. I. Vernadsky about noosphere. Keywords: city as an organism, energy balance, metabolism, free energy, resource flows, urban environment, entropy.